DEPENDENCE BETWEEN BODY-STRUCTURE, CARDIOVASCULAR FUNCTIONAL PARAMETERS, CHOLESTEROL LEVEL AMD THE TYPE OF EVOLVEMENT CONSTITUTION OF MATURE AND ELDERLY FEMALES - Filatova, O.; Voronina, I.; Lebiodko, T. (Acta Biologica Sibirica, 2016)
We measured anthropometric parameters, calculated the index of trohantern, such as the definition of the constitutional evolution of the aged organism on examples of Shtefko (1929) and Vasilchenko (1990), as well as the study of serum total cholesterol and functional indices of the cardiovascular system in women of the second period of mature and elderly. In individuals with extremes trohantern, index (both low and high) showed a statistically significant of higher level of total serum cholesterol. In the studied groups of women the value of BMI increases with index of trohantern generally is in the range above the 90th percentile, which is associated with obesity, exceeds the characteristic of the metabolic syndrome (30 kg/m2). Women with low and high values of index of trohantern tended to increase body fat. In individuals with extremes trohantern index (both low and high) revealed the predominance of influence on cardiovascular parasympathetic autonomic nervous system, the higher values of arterial diastolic pressure due to increased peripheral vascular tone. In groups with high trohantern index values indicate the adaptive capacity of poor adaptation. Identified two groups of people with the highest level of total serum cholesterol, having a complex out somatic characteristics: a group of people with values trohantern index < 1.91, overweight, increased fat deposition in the abdomen, a second group of people with values trohantern index of> 2.03, the excess body mass, increased fat deposition on the hips.